Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/app11031217
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Acetification Stage in the Production of Wine Vinegar by Use of Two Serial Bioreactors

Abstract: In the scope of a broader study about wine acetification, previous works concluded that using a single bioreactor hindered simultaneously reaching high productivities with high substrate consumption and the use of two serially arranged bioreactors (TSAB) could achieve such goal. Then, the aim of this work is the optimization, using Karush–Kuhn–Tucker (KKT) conditions, of this TSAB using polynomial models previously obtained. The ranges for the operational variables leading to either maximum and minimum mean ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Vinegar elaboration can be carried out by either solid-state fermentation (SSF) or liquid fermentation, with the latter including numerous techniques implemented in Western and European countries, mainly surface and submerged cultures [5,7]. The submerged culture is one of the main systems used to produce vinegar on an industrial scale [7][8][9]52].…”
Section: Systems Of Vinegar Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vinegar elaboration can be carried out by either solid-state fermentation (SSF) or liquid fermentation, with the latter including numerous techniques implemented in Western and European countries, mainly surface and submerged cultures [5,7]. The submerged culture is one of the main systems used to produce vinegar on an industrial scale [7][8][9]52].…”
Section: Systems Of Vinegar Productionmentioning
confidence: 99%
“…This system also allows for obtaining high-strength vinegars that may reach high acidity levels [up to 15% (w/v)]. With the high demand for these products, it may be necessary to use dual-stage high-strength processes in which two fermentation tanks are operated in a synchronous mode, thus even achieving acetic acid concentrations above 20% (w/v) [9]. In this way, the stressful environment to which AAB are subjected detracts from the overall acetification rate [5].…”
Section: Operating Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vinegar is likely one of the most appreciated products in the fermented food industry and one of the most economically important products obtained from AAB [ 5 , 9 ]. For this reason, among others, much of the research on the metabolism of AAB is aimed at improving the procedures for obtaining this product [ 10 , 11 , 12 ]. Because diverse AAB species may also metabolize sugars and sugar alcohols, the role of membrane-bound soluble dehydrogenases is attracting increasing interest from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of studies that we could classify in this context can be found in other publications of this book. For example, [8,9] deal with the study and modeling of an alternative way of working in the acetification stage of the wine vinegar bioprocess, a product with multiple uses and great importance: For instance, it is a high-quality condiment. For another example, see the publication [10], which deals with the study of the influence of operational variables, temperature, and time on the properties and durability of the processing of another food, sous vide chicken breast fillets; this case is an example of the need to optimize processing conditions in order to reduce the generation of waste from food that has already been prepared and not consumed.…”
mentioning
confidence: 99%